Dough Re Mi Bakery / Khadijah Aryani Khalid ... [et al.] - Khalid, Khadijah Aryani; Mokhtar, Nur Aqilah; Aminuddin, Nurul Iwany Wafa; Mohamad Rosni, Mia Batrisyia; Zainal, Mariah Qistina (2025)
The Dough Re-Mi Bakery is the only bakery that creates a wonderful and inventive dessert experience by combining the unique flavours of premium ice creams and melon buns inspired by Japan. Our bakery will open on 1 February 2025 and operates as a partnership. It is conveniently located in Seremban, Negeri Sembilan. In the food industry, our goal is to close a market gap by providing premium, affordable delicious foods that are distinct from more conventional options. Dough Re-Mi Bakery is positioned to set trends in the local dessert market by emphasizing creativeness and client delight. There are several factors in selecting the proposed business. First and foremost, a major factor was a growing demand for innovative and unique desserts. Premium ice cream and melon buns which is inspired by Japan are becoming more and more popular among customers who want unique foods. This demand presents a great opportunity to offer business that satisfy current tastes while introducing something fresh to the market. Second, we discovered an important need in the local market for companies who sell ice cream and melon buns together. This concept is rare and mainly unknown in the area. We have a great chance to build a unique identity in the food sector since it is rare. Thirdly, we differentiate ourselves from opponents with our unique selling proposition. By combining the affordability of our products with rich flavours and premium ingredients will produce a taste that attracts to a wide variety of consumers. This uniqueness guarantees that our brand will always know and competitive.